Candida albicans in Children with Early Childhood Caries: Scoping Review - Ajeng Krisna; Tri Putriany Agustin; F. Loes D. Sjahruddin (Indonesian Journal Publisher, 2026)
Early Childhood This scoping review aims to summarize scientific evidance regarding the presence, quantity, and role of Candida albicans in children with ECC and caries-free. A literature search was conducted using the Pubmed and Google Scholar database using the Preferres Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method. Both databases yielded 339 journals. All journals were then screened for eligibility, leaving six journals that met the research criteria. The results showed that C. albicans plays a significant role in the development of ECC, with a higher prevalence of C. albicans in children with ECC. Further research with longitudinal design is needed to improve understanding of etiology, prevention, and management of ECC.